2021
DOI: 10.1002/advs.202003164
|View full text |Cite
|
Sign up to set email alerts
|

Temporarily Epigenetic Repression in Bergmann Glia Regulates the Migration of Granule Cells

Abstract: Forming tight interaction with both Purkinje and granule cells (GCs), Bergmann glia (BG) are essential for cerebellar morphogenesis and neuronal homeostasis. However, how BG act in this process is unclear without comprehensive transcriptome landscape of BG. Here, high temporal-resolution investigation of transcriptomes with FACS-sorted BG revealed the dynamic expression of genes within given functions and pathways enabled BG to assist neural migration and construct neuron-glia network. It is found that the pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…7e). It has been reported that the three genes regulate the function of Purkinje cells [31][32][33] . Therefore, the specific expression patterns of these three genes indicate that this narrow region (cluster 12) is composed of Purkinje cells, which is consistent with the existing reports that the mature cerebellar cortex is composed of three layers: inner granular layer, Purkinje cell layer and molecular layer 34 .…”
Section: Deaplog Can Be Used In Identifying Degs In Spatial Transcrip...mentioning
confidence: 99%
“…7e). It has been reported that the three genes regulate the function of Purkinje cells [31][32][33] . Therefore, the specific expression patterns of these three genes indicate that this narrow region (cluster 12) is composed of Purkinje cells, which is consistent with the existing reports that the mature cerebellar cortex is composed of three layers: inner granular layer, Purkinje cell layer and molecular layer 34 .…”
Section: Deaplog Can Be Used In Identifying Degs In Spatial Transcrip...mentioning
confidence: 99%